Just Sustainabilities: Building Bridges and Breaking Barriers to Empower Employees for Inclusive Workplaces—Evidence from Ghana - Ernest Nkansah-Dwamena (Merits)
This study examines the critical role of inclusive, people-centered strategies in driving organizational sustainability, focusing on two key institutions in the Ashanti Region of Ghana: Presbyterian University College (PUC) and Presbyterian Agogo Women’s College of Education (APWCE). Employing a qualitative research design, including 100 interviews, five focus groups, and participant observations, this study investigates employee perspectives on Diversity, Equity, and Inclusion (DEI) practices in the workplace. The findings identify key empowerment strategies—flexible job roles, participatory decision-making, leadership development, and open communication—that enhance employee engagement and commitment to sustainability efforts. The findings also demonstrate employees’ vital role in advancing sustainability through involvement in green initiatives, community engagement, and integrating sustainability into core organizational practices. This contribution intellectually bridges the gap between DEI policies and their practical application, offering a nuanced understanding of how cultural and social dimensions influence sustainability in underexplored contexts like Ghana. It emphasizes aligning organizational values with employee well-being to enhance job satisfaction and retention, presenting actionable strategies for fostering innovation, resilience, and long-term success. The increasing global focus on sustainability and the growing need for inclusive practices in organizational settings underscores the timeliness of this manuscript. It offers a holistic, forward-thinking approach that is especially relevant for organizations navigating post-pandemic workplace dynamics and seeking to align sustainability with equity and inclusivity.